A ética como matriz rizomática fundamental para a proteção do direito internacional dos direitos humanos - Melo Junior, José Carlos Vieira de (2011)
Human rights belong to the International System of Human Rights had been marked by a cultural Eurocentric and therefore do not always achieve the necessary efficiency within the global society. In this sense, it is noted that throughout his historic statement, the International Law of Human Rights has brought all the forceful brand of culturalism focuses on Western ideals of social and political domination. In turn, the development of the International Trusteeship System of Human Rights occurred significantly after the Second World War did not have the power to depart from the prevailing legal positivism which allowed the emergence of a system not unlike the national models, ie the international legal order eventually developed on the basis of idealistic hegemonic. The metonymic reason based on the idea of totality in the form of order eventually to separate the law from its essential function for the global community, to be ethical behavior parameter. This expulsion ended up creating a situation of crisis paradigmatic of law in that it does not represent an effective mechanism of protection of Human Rights in the International System. Not constitute an instrument of imposition, but rather in dialogue through the contact between the various top of each culture. The present research aims to analyze the various factors so that eventually created the situation earlier, as well as to examine whether the rescue of Ethics may direct the restructuring of this system of rights, such as new core paradigm. It is not intended to rescue the parameters rationalist ethics of modernity, but which has an Ethics in otherness, understood as respect to the cosmic, the corporeality, life, justice, solidarity, intercultural, freedom and equality, rhizomatic principles as fundamental to its founding roots. We must point out that globalization is an irreversible phenomenon and that the contact between diametrically different cultures tend to develop more and more, so it is important to place the Ethics as a matrix of Fundamental Human Rights as a central theme of this work.